Skepticism in Hume’s Politics and Histories - Fosl, Peter S. (Araucaria, 2024)
This essay argues that Hume’s political and historical thought is well read as skeptical and skeptical in a way that roots it deeply in the Hellenistic traditions of both Pyrrhonian and Academical thought. It deploys skeptical instruments to undermine political rationalism as well as theologically and metaphysically political ideologies. (1) Hume’s is politics of opinion (doxa) and (2) appearance (phainomena). It labors to oppose faction and enthusiasm and generate (3) suspension (epochê), (4) balance (isosthenia), (5) tranquility (ataraxia), and (6) moderation (metriopatheia, moderatio). Because Hume advocate the use of reflectively generated but epistemically and metaphysically suspensive general rules, his political thought is not intrinsically conservative. While it valorizes stability and peace, Humean politics accepts a contested and open-ended (zetesis) political order, one that requires continuous maintenance and revision but does not pretend to any ultimate or final progress or end.